Receptive skills: reading & listening (ReaL) resource pack with app support / Nur Ain Abdul Malek ... [et al.] - Abdul Malek, Nur Ain; Che Hassan, Nor Syamimi Iliani; Mohammad Nor, Nor Hairunnisa; Kamarudin, Hanis (Universiti Teknologi MARA Shah Alam, 2018)
Educators all over the world have been incorporating smartphones specifically by using mobile applications (apps) in teaching. However, many educators encourage students to use smartphones especially for independent learning without any guidance. It is easy to assume that students would know how to use a certain app on their own. Barrs (2011) asserts that students demonstrate greater interest to continue self-directed learning using mobile devices when they are provided detailed guidance and explanation on how to use smartphone appropriately in classroom settings. This suggests that guided lessons using apps may increase the level of effectiveness in language teaching and learning. The objectives of the resource pack designed are to offer guided approach to the use of apps in language classrooms and to provide support materials to consolidate the lessons. Meanwhile, the novelty lies in the comprehensiveness of the lesson plans and materials while incorporating new technology in the classroom. The resource pack will give a valuable contribution to instructors in the teaching of English particularly on receptive skills like reading and listening. The development of this resource pack which is based on two apps: NST Mobile and LEB English is timely to educators who have interest in incorporating mobile devices in language teaching. Basically, this resource pack underscores a compilation of exciting and meaningful lesson plans meant for educators to conduct listening and reading instructions. Knowing time constraints often experienced by educators in preparing for their classes, worksheets are also included for the proposed lesson plans so that learning outcomes can be achieved at the end of the lessons.